2020
DOI: 10.3386/w26749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prescription Opioids and Prescription Opioid Control Policies on Infant Health

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…More recent studies distinguish between voluntary and mandatory access PDMPs, and provide more definitive evidence that the latter reduced prescription opioid misuse (Ali et al, 2017;Buchmueller and Carey, 2018;Deiana and Giua, 2018;Bao et al, 2018;Grecu et al, 2019;Mallatt, 2019Mallatt, , 2020bKaestner and Ziedan, 2019;Wen et al, 2019;Ziedan and Kaestner, 2020). For example, Grecu et al (2019) show that, following adoption of a mandatory PDMP, the number of admissions to substance use disorder treatment related to opioid use decreases by 20 to 25 percent, although reductions only emerge two years post-policy.…”
Section: Prescription Drug Monitoring Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies distinguish between voluntary and mandatory access PDMPs, and provide more definitive evidence that the latter reduced prescription opioid misuse (Ali et al, 2017;Buchmueller and Carey, 2018;Deiana and Giua, 2018;Bao et al, 2018;Grecu et al, 2019;Mallatt, 2019Mallatt, , 2020bKaestner and Ziedan, 2019;Wen et al, 2019;Ziedan and Kaestner, 2020). For example, Grecu et al (2019) show that, following adoption of a mandatory PDMP, the number of admissions to substance use disorder treatment related to opioid use decreases by 20 to 25 percent, although reductions only emerge two years post-policy.…”
Section: Prescription Drug Monitoring Programsmentioning
confidence: 99%
“…These policies appear to be effective in reducing prescription opioid use. Using government data on sales of scheduled prescription medications, Ziedan and Kaestner (2020) document 15 to 50 percent declines in prescription opioid sales after implementation of a PMCL. Early evidence from Florida and Texas suggest these targeted efforts are effective at curbing prescribing and reducing harmful secondary outcomes like overdoses (Chang et al, 2016;Lyapustina et al, 2016;Mallatt, 2020b;Meinhofer, 2016;Rutkow et al, 2015).…”
Section: Other Supply-side Policiesmentioning
confidence: 99%
“…More recent studies distinguish between voluntary and mandatory access PDMPs, and provide more definitive evidence that the latter reduced prescription opioid misuse (Ali et al, 2017;Buchmueller and Carey, 2018;Deiana and Giua, 2018;Bao et al, 2018;Grecu et al, 2019;Mallatt, 2019Mallatt, , 2020bKaestner and Ziedan, 2019;Wen et al, 2019;Ziedan and Kaestner, 2020). For example, Grecu et al (2019) show that, following adoption of a mandatory PDMP, the number of admissions to substance use disorder treatment related to opioid use decreases by 20 to 25 percent, although reductions only emerge two years post-policy.…”
Section: Prescription Drug Monitoring Programsmentioning
confidence: 99%
“…While earlier PDMP studies found mixed results (eg Meara et al 2016 find no change in various measure of opioid use after adoption of a PDMP, but Kilby 2016 finds a 12% decline in opioid related mortality following a PDMP), more recent research has distinguished between mandatory and non mandatory PDMPs and find that mandatory policies are effective at reducing prescription opioid misuse (Deiana and Giua, 2018;Bao et al, 2018;Mallatt, 2018;Buchmueller and Carey, 2018a;Grecu et al, 2019;Ali et al, 2017;Ziedan and Kaestner, 2020;Kaestner and Ziedan, 2019;Wen et al, 2019). There is also evidence that even if there is no prior opioid use to query in the system, prescribers may reduce use because of the hassle cost involved or because it has become more salient as a topic (Alpert et al, 2020;Sacks et al, 2019).…”
mentioning
confidence: 99%
“…Pill mill laws impose stricter policies on pain management clinics that dispense opioids, and appear to have reduced supply Deiana and Giua (2018); Popovici et al (2018); Ziedan and Kaestner (2020). This suggests that state level policy to restrict opioids have reduced supply.…”
mentioning
confidence: 99%